Development of the corticospinal and callosal tracts from extremely premature birth up to 2 years of age - Braga, Rodrigo M.; Roze, Elise; Ball, Gareth; Merchant, Nazakat; Tusor, Nora; Arichi, Tomoki; Edwards, David; Rueckert, Daniel; Counsell, Serena J. (PLoS ONE, 2015)
White matter tracts mature asymmetrically during development, and this development can be studied using diffusion magnetic resonance imaging. The aims of this study were i. to generate dynamic population-averaged white matter registration templates covering in detail the period from 25 weeks gestational age to term, and extending to 2 years of age based on DTI and fractional anisotropy, ii. to produce tract-specific probability maps of the corticospinal tracts, forceps major and forceps minor using probabilistic tractography, and iii. to assess the development of these tracts throughout this critical period of neurodevelopment. We found evidence for asymmetric development across the fiber bundles studied, with the corticospinal tracts showing earlier maturation (as measured by fractional anisotropy) but slower volumetric growth compared to the callosal fibers.We also found evidence for an anterior to posterior gradient in white matter microstructure development (as measured by mean diffusivity) in the callosal fibers, with the posterior forceps major developing at a faster rate than the anterior forceps minor in this age range. Finally, we report a protocol for delineating callosal and corticospinal fibers in extremely premature cohorts, and make available population-averaged registration templates and a probabilistic tract atlas which we hope will be useful for future neonatal and infant white-matter imaging studies.
CRIS-Team Scopus Importer:2023-03-08